A Tale of Three Countries: Italian, Spanish and Swiss Manufacturing Operations in China - Valeria Gattai (Fondazione Eni Enrico Mattei (FEEM), 2006)
In this paper we investigate the choice of FDI versus joint-venture, made by Italian, Spanish and Swiss multinationals in China, as shaped by the risk of Dissipation of Intangible Assets. Probit estimates, based on an entirely new firm-level dataset, constructed by the author, show that FDI is more likely to emerge when know-how easily spills over - namely for firms endowed with more Intangible Assets or belonging to high tech sectors - in line with the theoretical expectations.
Keywords: F23; C25; O53; 330; Intangible Assets; Internalisation; FDI; Joint-venture; China